Pengaruh Perputaran Modal Kerja, Perputaran Kas, Perputaran Persediaan dan Perputaran Total Aset Terhadap Tingkat Profitabilitas Badan Usaha Milik Desa untuk Meningkatan Pendapatan Asli Desa Tahun 2019-2020 (Studi pada Badan Usaha Milik Desa Se-Kabupaten Buleleng) - Dewi, Ni Luh Sucitra; Diatmika, I Putu Gede (Universitas Pendidikan Ganesha, 2021)
The study aimed at finding out the effect working capital turnover, cash turnover, inventory turnover, total asset turnover on the profitability of village-owned enterprises in Buleleng regency. This study was conducted based on a quantitative approach by involving 16 village-owned enterprises as the sampls which werw selected based on purposive sampling technique. The data were obtained from secondary sources by using documentation method, and analyzed by using a multiple regression supported by SPSS version 25.0 for Windows. The result indicated that (1) the level of working capital turnover had a negative and not significant on profitability, (2) the level of cash turnover had a positive and significant on profitability, (3) the level of inventory turnover had a positive and not significant on plofitability, (4) the level of total asset turnover had a negative and significant, and (5) the level of working capital turnover, cash turnover, inventory turnover, and total asset turnover of employee had a simultaneous significant effect on profitability. The results of this study have implications for BUMDes in managing BUMDes finances so that they are better and more optimal.Keywords: Working Capital Turnover, Cash Turnover, Inventory Turnover, Total Asset Turnover, Profitability, and BUMDes